Decrease in sperm number after treatment of rats with Austroplenckia populnea - Mazaro, R.; Di Stasi, L. C.; Vieira, S. A.; Kempinas, W. D. (Elsevier B.V., 2000)
The purpose of this study was to evaluate the effects of a hexanic extract (HE) made from leaves of A. populnea collected in Botucatu, State of São Paulo, and Nova Lima, State of Minas Gerais, Brazil, at a range of doses during 7 and 14 days, on the male reproductive system of rats. The treatment did not affect the body weight, nor absolute organ weight. The serum testosterone levels, testicular sperm head counts, daily sperm production, and sperm morphology did not differ from that of the control groups. The spermatogenesis and the morphometric parameters of cauda epididymidis were not affected by the treatment. Cauda epididymis sperm number was significantly reduced in the group that received HE of Nova Lima, 1 g/kg/day, during 14 days, from the control group. (C) 2000 Elsevier B.V. All rights reserved.
Keywords: Austroplenckia populnea; Celastraceae; male reproductive system; epididymis; sperm; oligospermy